The Road to the Land of the Mother of God A History of the Interoceanic Highway in Peru. - Perz, Stephen G. (University of Nebraska Press, 2023)
Through more than five hundred years of the history of Peru's Interoceanic Highway, this book shows how the purposes, portrayals, and importance of roads change between historical periods, and thus why roads bring many more impacts and costs than their advocates and critics generally anticipate.